Hécuba, de Eurípides: uma perspectiva de tradução - Andreza Sara Caetano de Avelar Moreira (2015)
This work is composed of organised reflections about the author's time, and about himself, his life and conceptions of society. Furthermore, we search to analyze the rhetoric in the play and we attempt to create a psychological profile of the characters involved. All of our peripheral scope was made due to the translation of Hecuba, by Euripides, a translation that intends to be accessible and fluid, conversational and, mainly, directed towards the representation on stage.